Estimating th household willingness to pay for the preservation of Talomo-Lipadas watersheds - Papica, Karinna E.
The study attempted to determine how much the residential water users of Talomo-Lipadas watersheds were willing to pay for the rehabilitation, protection and management of the watersheds. Primary data were collected from 55 randomly selected respondents from Poblacion, Davao City, using a questionaire specifically designed for the study. The survey questionaire used in the study consisted of four parts; introduction, socio-economic and demographic information, awareness and attitude towards the Talomo-Lipadas watershed management, and willingness to pay. The results revealed that 85% of the respondents were willing to pay for the program and the maen WTP value was P55.09 per month. With the use of the Ordinary Least Squares (OLS) model, it was found that the total household monthly income greatly greatly influenced the WTP values of the respondents. A household with high monthly income expressed a relatively higher WTP than those with lower income. The major limitation of the study is that of having a small sample size, which was only 55 and a small R-squared value.